Pengaruh Gender dan Kemampuan Akademik terhadap Literasi Keuangan Mahasiswa pada Mahasiswa Akuntansi di Perguruan Tinggi Indonesia - Pradnyaparamita, Agatha Bunga (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2024)
Finance is one of the main problems faced by every individual in modern society. Therefore, one must have a good understanding in managing finances. Financial literacy is knowledge, skills and beliefs that influence attitudes and behaviors to improve the quality of decision making and financial management in order to achieve prosperity. Many factors affect a person's level of financial literacy including gender and academic ability. This study aims to determine the influence of gender and academic ability on financial literacy. The research was conducted at FEB UKSW where a sample of 101 students was taken. The method used is multiple linear regression analysis. The results of this study show that simultaneously gender factors and academic ability have a significant effect on the level of financial literacy. In the partial test, gender and academic ability also have a significant effect.